An Evaluation of Medical Record Keeping Status to Assess Health Care Facilities for Hospitalized Patients In A Tertiary Care Hospital (KYAMC Journal, 2022)
Background: A patient’s medical record should provide accurate information on who the patient is and who provided health care; what, when, why and how services were provided; and the outcome of care and treatment.Objectives: The study was conducted with the objective of revealing the condition of medical audit of the inpatient department in Rangpur medical college hospital in short duration of time.Materials and Methods: A cross-sectional descriptive study was done in inpatient department in Rangpur Medical College & Hospital. This was carried out on 160 medical documents, interview with providers, record of hospital statistics & personal observation on physical facilities in indoor at the time of the study to find out in what extend medical record exist in patient service.Results: In inpatient department of Hospital, the generation and location of the form in all wards were inpatient, administrative office & type of the forms were mixed pattern. There was no electronic record system in the medicine department. They consisted of forms, sheet & register khata. Medical records were not filled of in most of the cases. A hundred and sixty records were checked where most of the components were not filled up completely (above 30% not filled up). The recording of hospital statistics were satisfactory and maintained regularly in the inpatient department.Conclusion: The standard of documentation by providers in inpatient medical records was found to be acceptable, with improvements required in a number of specific items.KYAMC Journal Vol. 13, No. 02, July 2022: 81-85